My yester-years : autobiography of an economist/banker Chief S.B. Falegan - Falegan, Samuel B. (Lagos: Bamboo House, 2013)
An autobiography of Chief S.B Falegan a renowned banker and economist with strong interest in international finance.
Includes index
oej 20/11/19
Loans
Keywords: Falegan, Samuel B; Autobiography; Nigeria